1987
DOI: 10.1063/1.453710
|View full text |Cite
|
Sign up to set email alerts
|

The density of supercooled water. II. Bulk samples cooled to the homogeneous nucleation limit

Abstract: We have measured the density of supercooled water (H2O) in the range −33.41≤T≤−5.23 °C. Our samples were held in glass capillary tubing with an approximate inside diameter of 0.3 mm=300 μ. These samples were prepared by Mossop’s method and could be cooled to their homogeneous nucleation limit before freezing. We compare our density data to other measurements using capillaries and demonstrate what appears to be an excess density in smaller capillaries which is inversely proportional to the capillary inside diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
202
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(214 citation statements)
references
References 13 publications
10
202
2
Order By: Relevance
“…Indeed recent experiments 6 identified the onset of ice crystallization to occur in a water cluster containing 275 water molecules at 90B115 K, and recent simulations 22 based on the mW water model have shown that ice formation can be avoided in a droplet of 1 nm in radius at 150 K. We note that our numerical results were obtained based on the mW water model that underestimates the density difference (2.3%) between ice and water at T m (as compared with the experimental value of 8.2% 29 . See Supplementary Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms2918contrasting
confidence: 39%
See 2 more Smart Citations
“…Indeed recent experiments 6 identified the onset of ice crystallization to occur in a water cluster containing 275 water molecules at 90B115 K, and recent simulations 22 based on the mW water model have shown that ice formation can be avoided in a droplet of 1 nm in radius at 150 K. We note that our numerical results were obtained based on the mW water model that underestimates the density difference (2.3%) between ice and water at T m (as compared with the experimental value of 8.2% 29 . See Supplementary Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms2918contrasting
confidence: 39%
“…As a summary of the results of our thermodynamic model, we constructed a temperature-radius diagram (Fig. 4) using the thermodynamic data of the mW water model 13 and real water 29,30 , to illustrate both the temperature and size effects on ice nucleation rate in supercooled water nanodroplets. At a given temperature, the diagram suggests that water droplets with radius greater than that indicated by the boundary would exhibit a bulk-like behaviour, that is, ice nucleation rates in droplets are within the statistical uncertainty of the calculated bulk ice nucleation rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that this anomalous line should run parallel to the homogeneous nucleation line on the experimentally inaccessible side. Since then, many static and dynamic quantities have been studied and shown to satisfy a power law relation at the lowest temperatures, as expected for such quantities near a spinodal [8][9][10][11][12][13][14]. However, theories which are not based on the existence of critical behavior in the supercooled region are also able to reproduce the experimental data with functional forms other than a power law [15].…”
Section: Introductionmentioning
confidence: 93%
“…The complex refractive index of m = 1.34 + i10 −9 measured by Segelstein (1981) for liquid water at 25 • C and λ = 490 nm was used as anchor point for calculating the temperature dependent refractive index of the supercooled water droplets. This was achieved by applying the Lorentz-Lorenz relation together with a parameterisation of the temperature dependence of the water density given by Hare and Sorensen (1987). As already mentioned in Sect.…”
Section: Supercooled Water Dropletsmentioning
confidence: 99%